The Danube near Vienna from the heights of Nusdorf - Heath, Charles 1785-1848 (engraver):::Creator::::::::::::; Batty, Robert, 1789-1848 (artist):::Contributor:::::::::::: (London; United Kingdom; Rodwell & Martin New Bond Street)
Color engraving with distant views of Vienna and the Danube River and Nussdorf in the foreground